A Pioneer Campus Center: The Creation of the University of Michigan's Human Sexuality Office (Studying the History of Higher Education Journal, 2024)
This essay focuses on the creation of the Human Sexuality Office at the University of Michigan, the first official LGBTQ+ center at a university in the United States. The Human Sexuality Office opened in the Fall of 1971 spearheaded by graduate student Jim Toy, but also with support from local LGBTQ+ groups and university staff, students, and faculty. This historical essay traces the opening of the Human Sexuality Office, the role of its main founder Jim Toy, the resistance against it, and its first year in operation. In addition, the essay provides an overview of the environment surrounding the office’s opening, including national attitudes and activism regarding the LGBTQ+ community during the 1960s and early 1970s. I rooted this historical analysis in primary and secondary documents from the University of Michigan’s Bentley Historical Library and its collection of documents related to the Human Sexuality Office, now known as the Spectrum Center, and its founder Jim Toy.
Keywords: Human Sexuality Office; Spectrum Center; first LBGTQ college center; Jim Toy; historical narrative